2003
DOI: 10.1093/ps/82.8.1313
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of elevated plasma corticosterone concentrations in broiler chickens. An alternative means by which to assess the physiological effects of stress

Abstract: Research on physical or psychological stress, in order to monitor objective parameters for animal welfare, is usually performed during experimental stress induction. To avoid treatment of animals with physical or physiological stress, addition of the stress-related hormone corticosterone to the drinking water, may serve as a practical alternative to reproducibly investigate hormone-related stress in broiler chickens. Rapid uptake of the hormone and distribution in the bloodstream were affirmed by elevated plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
100
0
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(120 citation statements)
references
References 23 publications
7
100
0
13
Order By: Relevance
“…Accordingly, it has been shown that poultry exposed to various stressful environments or procedures have lower antibody production in response to a variety of antigens including SRBC (Siegel, 1985). Similarly, exposure to continuous infusions of ACTH (Mumma et al, 2006) or dietary corticosterone (Post et al, 2003), in order to mimic chronic stress, suppressed antibody responses to immunization with experimental antigens such as SRBC (Mumma et al, 2006) and vaccines used commercially, for example, infectious bronchitis virus vaccine (Shini et al, 2008). On the other hand, reducing stress during the laying period (Zulkifli et al, 2002) and enriching the cage environment (El-Lethey et al, 2000) led to increased anti-SRBC antibody titres.…”
mentioning
confidence: 99%
“…Accordingly, it has been shown that poultry exposed to various stressful environments or procedures have lower antibody production in response to a variety of antigens including SRBC (Siegel, 1985). Similarly, exposure to continuous infusions of ACTH (Mumma et al, 2006) or dietary corticosterone (Post et al, 2003), in order to mimic chronic stress, suppressed antibody responses to immunization with experimental antigens such as SRBC (Mumma et al, 2006) and vaccines used commercially, for example, infectious bronchitis virus vaccine (Shini et al, 2008). On the other hand, reducing stress during the laying period (Zulkifli et al, 2002) and enriching the cage environment (El-Lethey et al, 2000) led to increased anti-SRBC antibody titres.…”
mentioning
confidence: 99%
“…Normally stress, and especially stress for longer periods (Hangalapura et al, 2003), has a negative impact on body weight gain, which may be a consequence of elevated corticosterone levels. It has been shown that feeding corticosterone to chickens reduces body weight gain (Post et al, 2003). The positive body weight gain in Hellevad chickens in treatment H2 in the present experiment might be caused by a reduced level of corticosterone or by reduced sensitivity to corticosterone as a reaction to the gentle stressor.…”
Section: Discussionmentioning
confidence: 44%
“…However, this was not the case, as there was no significant difference in E. coli antibody titres between the chicken strains 3 weeks after infection. Others have found that stress (El-Lethey et al, 2003) and the major stress hormone, corticosterone (Post et al, 2003), influence antibody responses. However, this was dependent on the antigen tested (El-Lethey et al, 2003) suggesting that the antigen tested in the present study might be of a stress-resistant character, or that the antigen load has actually been too small to provoke the humoral differences or that the increase in MHCII1 lymphocytes reflected an increased activation of T-cells rather than an increased % of B-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Buyse et al, 1987;Post et al, 2003;Lin et al, 2006), inflict involution of spleen (Malheiros et al, 2003;Post et al, 2003), and increase the mass of adrenals (Selye, 1950;see Mormede et al, 2007) and liver (Buyse et al, 1987;Malheiros et al, 2003;Lin et al, 2006). The mass of heart, for its part, can Table 2 Percentage of animals with bite marks on the leather side of their skin, severity of bite scars on a subjective scale where 0 denotes 'no bite marks' and 5 'almost the whole skin covered with marks' (mean 6 s.e.…”
Section: Discussionmentioning
confidence: 99%